EDUKASI MENGENAI KEPEKAAN PEMILAHAN SAMPAH RUMAH TANGGA DI PERUM ABDI NEGARA MANGKUBUMI - Kamila, Yuke Najma; Aprilliani, Zahra Nur; Maharani, Putri; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Garbage is an issue of concern in the community because there are still many less sensitive to cleanliness around it. Efforts by local authorities have also not been able to wake the public up to the importance of cleanliness. A major factor that needs to be recognized is self - examination by handling garbage in its proper place at the next level by sorting garbage according to its type. The selection of garbage isa step-by-step separation of litter of different kinds, there is organic garbage, inorganic garbage, to residue garbage. Selection has several benefits: to reduce pollution, to produce reusable products, to produce some energy through compost fertilizers that can be used as crops. The one that can be treated is the racyclable waste, and the one that cannot be treated is the non-racyclable waste.